Faktor Yang Mempengaruhi Kepatuhan Pengobatan Pasien Hipertensi pada Masa Pandemi Covid-19 - Haeruddin Haeruddin; Ulfarica Desi Dwi Ananda; Suharni Andi Fachrin; Rezky Aulia Yusuf (Sarana Ilmu Indonesia (salnesia), 2021)
Hypertension has a negative impact on various health complications and economic burdens associated with decreased productivity. This has become even more complicated with the Covid-19 pandemic. This study aimed to analyze Factors influencing medication adherence of hypertension patients during the Covid-19 pandemic at the Makkasau Health Center, Ujung Pandang District, Makassar City. The type of research used was quantitative by using path analysis. Sampling was done by the purposive sampling method. The results of the study were found there were no effect of work status (p=0,346) and lifestyle (p=0,595) on increasing motivation and adherence to treatment of hypertension patients during the Covid-19, there were effect of family support (p=0,003), the level of knowledge (p=0,007), and the role of health workers (p=0,008) through increasing motivation on medication adherence of hypertension patients during the Covid-19. The conclusion of this study is that there is no effect between work, lifestyle increasing motivation, and adherence to treatment for hypertension patients during the Covid-19 pandemic and there is effective family support, knowledge, the role of health workers through increasing motivation for adherence to treatment of hypertension patients during the Covid-19 pandemic. So, it is recommended to subjekts to routinely control blood pressure and take medication according to the prescription that has been given in order to minimize the occurrence of complications of other diseases.